Rancang Bangun Sistem Kendali dan Monitoring Rumah Tinggal Menggunakan Smartphone Berbasis Mikrokontroler di Sukaharja Kabupaten Ketapang - Syarif Ishak Alkadri (Politeknosains, 2019)
A recent technological development in many developments such as small shophouses and residential houses has made practitioners create ideas that are very useful for society in life today, especially the number of theft cases that target residential houses. The occurrence of the theft was due to a lack of security, causing the thieves to intend to look for opportunities to enter the house. To overcome this problem arises the design and control systems using a smartphone-based microcontroller. The open source operating system on an Android smartphone can be used to make a light controller and servo motor application to play CCTV using Arduino UNO (Microcontroller AT Mega 328). Android applications are used as input commands to the microcontroller circuit via a bluetooth module connector. The servo motor controller system for playing CCTV uses 3 output pins on the microcontroller, and for the light controller system uses output pins 3,4,5,6,7,9,10,11,13 on the microcontroller, the light controller system pins are connected with 2.2K ohm resistor for lights with a current (DC), and for lamps with a current (AC) using relay modules, relay modules function as a switch. The results obtained by the servo motor can rotate 180º and 9 lights can work controlled with an Android smartphone.